Nowe metody stosowane w nauczaniu języka polskiego jako obcego na poziomie A1 (zarys problematyki) - Kulka, Dobrawa (Dydaktyka Polonistyczna, 2015)
The article is an attempt to look at the contemporary methods of teaching the Polish language as a foreign language. On the basis of long practice and huge experience, the author fishes out some of the most interesting and helpful methods when working with students. It consists of a set of clues of how to use materials accessible in the Internet, newspapers and textbooks in order to adjust them to one’s own teaching targets and also how to create unique teaching toolbox. The article encourages the Polish language lectors both to search for new and individual ways of teaching and to compile existing methods of teaching to adjust them to the needs, expectations, language level and predisposition of students.